Cephalopharyngeal geometric morphometrics in three blowfly species (Diptera: Calliphoridae) - Nuñez, Jose A. (2016)
The blowflies (Diptera: Calliphoridae) comprise a group of medical and forensic importance because some species are responsible for myiasis and immature stages of several species feed on corpses and show preference for certain stages of decomposition. In both cases, the correct taxonomic determination is a crucial aspect for a medical or forensic investigation. The geometric morphometrics is a recent tool that describes the shape variation, although this technique has been used in adult blowfly, it has not been evaluated in immature. The goal of this study was to analyze the variations on cephalopharyngeal morphometrics, to support the identification of forensic immature flies. For this we photographed a total of 101 cephalopharyngeal skeletons from Chrysomya albiceps (n=34), C. megacephala (n=34) and Lucilia cuprina (n=33). Landmark coordinate (x, y) configurations were registered and aligned by Generalized Procrustes Analysis. Canonical Variates Analysis (CVA) were implemented with proportions of re-classified groups and MANOVA. Statistical analysis of variance found significant differences in centroid size (Kruskal-Wallis). The CVA showed significant separation, and a posteriori re-classification was 100% correctly assigned. The main differences between the three species were localized on: base of parastomal bar, apical tooth, clipeal arc, concavity of the pharyngeal sclerite, and union between hypostomal sclerite and the mouth hook. These differences could be useful as additional tools for larvae taxonomic identification; however, more studies are needed that include a more complete species representation in Calliphoridae.